Preparation of neodymium hydroxide nanorods and neodymium oxide nanorods by a hydrothermal method - N. Ekthammathat (2018)
© 2015, Inst Materials Physics. All rights reserved. One dimensional Nd(OH)3 nanorods were successfully prepared through a 180 oC and 20 h hydrothermal reaction. Subsequently, the Nd(OH)3 nanorods were calcined at 450–600 oC for 2 h. Their phases and morphologies were characterized by XRD, SEM and TEM. The XRD patterns revealed the hexagonal Nd(OH)3 phase of the precursor and the hexagonal Nd2O3 phase of the final product. Upon calcination at 550 °C and above for 2 h, the hexagonal Nd(OH)3 nanorods were transformed into the hexagonal Nd2O3 nanorods with the shape remained unchanged. In this research, uniform Nd(OH)3 nanorods and Nd2O3 nanorods with the increase in size by the high temperature calcination were detected.